Processes for Obtaining Quality Silk Raw Materials From Industrial Silkworm Cocoons - M. B. Soliyeva; N. N. No'monov (Central Asian Journal of Theoretical and Applied Science, 2022)
One of the important tasks in increasing the production of silk fabrics in our country is to preserve the technological properties of cocoons, the main raw material of the industry, to improve the technology of their primary processing to obtain raw silk in accordance with world standards. Therefore, any scientific research in this area has its own important relevance.